2010
DOI: 10.1002/adma.200903091
|View full text |Cite
|
Sign up to set email alerts
|

HPW/MCM‐41 Phosphotungstic Acid/Mesoporous Silica Composites as Novel Proton‐Exchange Membranes for Elevated‐Temperature Fuel Cells

Abstract: Proton-exchange membrane and direct methanol fuel cells (PEMFCs and DMFCs) have attracted much attention as clean energy sources for various applications, such as electric vehicles, portable electronics, and domestic power generation, because of their high power density, high efficiency, and low greenhouse gas emission. [1][2][3][4][5] Especially, the operation of PEMFCs and DMFCs at temperatures above 100 8C is considered to have many advantages, such as the elimination of CO poisoning of the platinum electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 34 publications
(46 reference statements)
5
105
0
Order By: Relevance
“…The small angle X-ray scattering (SAXS) of meso-SiO2 after PWA impregnation shows reduced intensity of the meso-SiO2 matrix (Fig.1F), indicating aggregation of PWA within the meso-SiO2 structure. 35 Moreover, the scattering peak position after PWA impregnation remains unchanged, suggesting structural integrity. The N2 adsorption/desorption isotherms of meso-SiO2 and PWA-meso-SiO2 show type IV adsorption curves with capillary condensation effect for the mesoporous structure and H 1 type hysteresis for cylindrical mesoporous structures ( After surface modification of PWA-meso-SiO2 with dequalinium chloride hydrate (Scheme S1, ESI † ) to improve the dispersion in the PBI solution, homogenous composite membranes were obtained in the low PWA-meso-SiO2 loading range up to 15 wt%, as evidenced from the cross-sectional scanning electron microscopy imaging (Fig.…”
mentioning
confidence: 98%
“…The small angle X-ray scattering (SAXS) of meso-SiO2 after PWA impregnation shows reduced intensity of the meso-SiO2 matrix (Fig.1F), indicating aggregation of PWA within the meso-SiO2 structure. 35 Moreover, the scattering peak position after PWA impregnation remains unchanged, suggesting structural integrity. The N2 adsorption/desorption isotherms of meso-SiO2 and PWA-meso-SiO2 show type IV adsorption curves with capillary condensation effect for the mesoporous structure and H 1 type hysteresis for cylindrical mesoporous structures ( After surface modification of PWA-meso-SiO2 with dequalinium chloride hydrate (Scheme S1, ESI † ) to improve the dispersion in the PBI solution, homogenous composite membranes were obtained in the low PWA-meso-SiO2 loading range up to 15 wt%, as evidenced from the cross-sectional scanning electron microscopy imaging (Fig.…”
mentioning
confidence: 98%
“…[50,51]. The position of the scattering peaks for HPW/MCM-41 powders remains the same as that of the pristine MCM-41 without any HPW impregnated, indicating that HPW has coalesced well into the mesoporous structure of MCM-41 [5,6]. This is explained by the occurrence of the relative intensities of scattering peaks of the as-assembled HPW/MCM-41 powders, which decreased significantly with the increase of HPW content until the peak disappeared/almost disappeared [6].…”
Section: Conductivity and Cell Performance Measurementsmentioning
confidence: 57%
“…In the case of MCM-41-HPW15-m membrane, the conductivity was 2.4 Â 10 À3 S cm À1 and 7.7 Â 10 À3 S cm À1 at 25 C and 80 C, respectively. Lu et al have reported that the proton conductivity of the pristine MCM-41 host is very low, i.e., 5.1 Â 10 À6 S cm À1 [5]. This indicates that the transport of protons through the pure mesoporous silica via surface hydroxyl groups is very difficult.…”
Section: Microstructure Solvent Uptake and Conductivity Of Mcm-41-hpmentioning
confidence: 93%
See 2 more Smart Citations